THE BANKING UNION - OPPORTUNITIES OR LIMITATIONS FOR THE FINANCIAL SECTOR - Jacek BINDA (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
Public debate on the effectiveness of the models of financial market supervision during the 2007-2011 global crisis found its final reforms leading to the creation of a banking union. Among the recurring accusations addressed to the financial supervisory institutions were, for example, their delayed reaction to the first signs of danger and not firm and ineffective measures undertaken to combat the crisis. The purpose of this paper is an attempt to present the actions taken by the EU to protect the banking system and the benefits of these changes for both the Euro area countries and other EU members, such as Poland. This paper is based on a review of available literature and own research. The conclusions of the paper indicate, inter alia, the need to reform the system of financial supervision, the need to improve attractiveness of the proposed solution - especially for countries that are not members of the Eurozone.